P550 Management of immunomodulators and biologic agents in pregnant patients with inflammatory bowel: results from the DUMBO registry of GETECCU. (21st January 2022) - Chaparro, M; Donday, M G; Rubio, S; Nuñez, A; Calviño Suarez, C; Madero, L; Figueira, M; Rivero, M; Pérez Martínez, I; Diz-Lois Palomares, M T; Huguet, J M; Marín Pedrosa, S; et al.
Abstract: Background: Most of the drugs approved for the treatment of inflammatory bowel disease (IBD) seem to be of low risk during pregnancy. However, clinicians' attitude to IBD treatments during pregnancy in clinical practice has been barely studied. Aim: Primary: To describe the management of immunomodulators and biologic agents prescribed for IBD (initiation and withdrawal) in a prospective registry of clinical practice. Secondary aims: To know the main reasons for drug discontinuation; and to evaluate the impact of drug withdrawal on IBD activity during pregnancy. Methods: Pregnant patients with IBD from DUMBO registry were included. DUMBO is a prospective, observational and multicentre registry, which enrols pregnant women with IBD over 5 years in 70 centres in Spain. The registry was kicked off in September 2019. Study protocol is summarized in figure 1. Results: So far, 580 pregnant women have been included in the registry; of them, 489 conceived at least 40 weeks before data extraction and were considered for the present analysis (Table 1). 98% of the pregnancies were singleton, and 2% were twin pregnancies. There were 4% of miscarriages, and 1% of elective abortions. The majority of patients were in remission at conception and throughout pregnancy. Patients' treatments during pregnancy are summarized in table 1; 20% of patients were exposed to thiopurines, 29% to biologics, and 10% to both biologics and thiopurines. No patient received methotrexate, cyclosporine, tacrolimus or tofacitinib during pregnancy. A minority of patients started a new drug during pregnancy: 3 patients (0.6%) started azathioprine, 2 (0.4%) adalimumab, 6 (1.2%) infliximab, and 1 (0.2%) ustekinumab. The proportion of patients who discontinued each drug, reasons for discontinuation, trimester of gestation at discontinuation and disease outcome, are summarized in table 2. The proportion of patients who discontinued each drug among those with the standard or the intensified dose, are summarized in table 3. Of noted, biologic agents were discontinued in over 1/3 of patients, while thiopurines were maintained in most cases (78% of those who interrupted thiopurines were maintained on biologics). No patient flared-up after drug discontinuation (Table 2); all but one patient who interrupted the treatment, were in remission at baseline Conclusion: Biologic agents (even anti-TNF agents) are withdrawn in a relatively high proportion of IBD patients during pregnancy, mainly due to clinicians' decision. The risk of relapse after drug discontinuation is low, probably due to adequate control of the disease activity already at conception.